2011
DOI: 10.1007/s00394-011-0280-6
|View full text |Cite
|
Sign up to set email alerts
|

Silk and silkworm pupa peptides suppress adipogenesis in preadipocytes and fat accumulation in rats fed a high-fat diet

Abstract: SP and SPP inhibit the differentiation of preadipocytes and adipogenesis by modulating signal transduction pathways and improve HFD-induced obesity by reducing lipid accumulation and the size of adipocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
45
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 35 publications
1
45
0
Order By: Relevance
“…In addition, that of the SP group significantly decreased compared to that of CON group (* p,0.05). Recent studies have reported that silk peptide ingestion is effective in weight loss for white mice (5,16,18). In the present study, a significant weight loss was also exhibited in the group with 2 wk of exercise and silk peptide intake (800 mg/ kg) compared to that of the control group.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, that of the SP group significantly decreased compared to that of CON group (* p,0.05). Recent studies have reported that silk peptide ingestion is effective in weight loss for white mice (5,16,18). In the present study, a significant weight loss was also exhibited in the group with 2 wk of exercise and silk peptide intake (800 mg/ kg) compared to that of the control group.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, SP promotes fat oxidation and increases energy expenditure (15,16). Additionally, in several rat and mouse model studies, food intake and body weight were decreased in rodents fed ad libitum (5,14,16).However, measurements in those studies have been conducted for analysis of blood profiles and hormones in mice. Accordingly, we investigated the effects of SP administration using an open circuit calorimetry system on resting energy expenditure and substrate utilization in resting mice for 24 h.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In 2012, Lee et al 8 . reported that treatment with 1 mg/mL SP + 0.2 nM insulin increases glucose uptake (124 ± 2.5%) via upregulation of glucose transporter type 4 (GLUT4) and decreases fat accumulation via upregulation of leptin in 3T3-L1 preadipocytes.…”
Section: Introductionmentioning
confidence: 99%